1990
DOI: 10.1136/gut.31.12.1350
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vasoactive intestinal peptide on cyclic adenosine monophosphate production in enterocytes isolated from human duodenal biopsy specimens.

Abstract: A modification of a cell isolation technique used in animal studies was developed to remove enterocytes from duodenal biopsy specimens. Citrate-ethylenediaminetetra-acetic acid treatment removed enterocytes from any underlying lamina propria and produced single cells and strips of cells. A mean (SEM) of 4-39 (2.06) x 106 cells was obtained from nine duodenal biopsy specimens. Enterocyte recovery was estimated enzymatically using alkaline phosphatase activity and was found to be 61%. Cytological assessment of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…More than 90% of cells isolated by the calcium chelation method employed were identified as epithelial cells, with preparations routinely containing Ͻ3% leukocytes. We have previously demonstrated that a highly purified population of enterocytes was produced using the same isolation technique and a different cytokeratin marker (30). It, therefore, seems most likely that the NOS activity measured in these preparations is derived from enterocytes with minimal or no contribution from contaminating leukocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 90% of cells isolated by the calcium chelation method employed were identified as epithelial cells, with preparations routinely containing Ͻ3% leukocytes. We have previously demonstrated that a highly purified population of enterocytes was produced using the same isolation technique and a different cytokeratin marker (30). It, therefore, seems most likely that the NOS activity measured in these preparations is derived from enterocytes with minimal or no contribution from contaminating leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Enterocytes were isolated using a modification of a method previously described (30). Biopsies were collected and washed twice in prewarmed sterile citrate buffer (in mM: 1.5 KCl, 96 NaCl, 27 Na citrate, 8 KH 2PO4, and 5.6 Na2HPO4, pH 7.4) before being transferred to a calcium-chelating buffer (in mM: 1.5 EDTA, 0.5 1,4-dithiothreitol, 10 NaH 2PO4, 154 NaCl) and incubated at 37°C for 30 min.…”
Section: Patientsmentioning
confidence: 99%
“…The neuropeptide VIP, widely distributed in specialized cells and nerves of the gut (Larsson et al 1976) and has been shown to stimulate duodenal mucosal bicarbonate secretion in the rat, cat and pig (Isenberg et al 1984, Flemstrom et al 1985 as well as in man (Wolosin et al 1989). VIP is a potent stimulator of cAMP formation in rat intestinal epithelium (Laburthe et al 1979) and in enterocytes isolated from human duodenal and jejunal biopsy specimens (Smith et al 1990, Hitchin et al 1991. However, in the cat jejunum in vivo VIP has been reported to not influence tissue cAMP concentration in villi or crypts (Eklund et al 1987).…”
Section: Discussionmentioning
confidence: 99%
“…exchange by a cAMPdependent protein kinase [22]. VIP and PGE2 were shown to act via receptors coupled to adenylate cyclase in iso lated enterocytes in the rat [23] and man [24], We have recently reported that VIP and PGE2 potently stimulate adenylate cyclase and protein kinase A in homogenized duodenal enterocytes, but secretin and PGF2(1 were only weak stimulants [21], This is consistent with the strong effects of PGE2 and VIP on duodenal bicarbonate secre tion in this study. We have recently described the pres ence on duodenal enterocytes of VIP receptors [25] and EP2 subtype receptors for PGE2 [15], All this is corrobora tive evidence for the role of cAMP in bicarbonate secre tion.…”
Section: Second Messengers O F Bicarbonate Secretionmentioning
confidence: 99%